Exserohilum turcicum em milho: caracterização morfológica e patológica, associação a sementes e sensibilidade a fungicidas - Rossi, Roberto Luis de (2012)
The northern corn leaf blotch, caused by the fungus Exserohilum turcicum (Et), has become an important disease in parts of Argentina and Brazil, in particular those with environment favorable for disease. Many companies conduct corn seed work in both countries, and there is usually exchange of genetic material in order to select hybrids better adapted to each region. Because of this, it is essential the availability of information in the pathosystem to guide management strategies. The objectives of this study were to: (i) compare the morphological characteristics of Et conidia, its pathogenicity in hybrid corn, isolated from Argentina and Brazil, (ii) develop a sensitive method for detection and quantification of the fungus infecting/infesting seed corn and popcorn, (iii) identify methodology for artificial seed corn inoculation and utilize the infected seeds to describe and quantify the transmission process from seeds to aerial organs, (iv) determine the mycelial sensitivity of Et ten isolates, five from Argentina and five in Brazil, six fungicides used in seed treatments. The tests were performed at the University of Passo Fundo during the years 2011 and 2012. Were measured and characterized 200 spores of each isolate. To confirm the fungus pathogenicity, corn plants were inoculated with the deposition of a conidia suspension of Et in the whorl and after two weeks quantified the number of lesions/leaf and the measured lesion length. We tested different media/methods for detection of pathogen in seeds using artificially infected seeds. The most sensitive method was used in commercial seed naturally infected and infested with Et. We tested different methods of seed inoculation and assessed the incidence of Et and germination and to describe the transmission to the aerial organs. The sensitivity mycelium was performed in vitro using petri dishes with culture medium potato dextrose agar (PDA) supplemented with concentrations of 0, 0.01, 0.1, 1, 10, 25 and 50 mg/L. On the average conidia measured 10-25 x 30-135 μm, with 2-8 septa, the measured characteristics matched those reported in the literature. The ten isolates produced an average of 2.5 lesions/leaf, was not seen significant differences in pathogenicity among the ten isolates. A semi-selective medium consisting of: i) streptomycin sulfate 500 mg/L, ii) neomycin sulfate 600 mg/L iii) carbendazim 60 mg/L, and iv) captan 30 mg/L, added to the medium lactose hydrolysed casein agar (LCHA) was selected. With the semi-selective medium Et fungus was detected in corn seeds naturally infected with 0.124% incidence. It was also determined and corn seed infestation with 1.04 conidia/seed. Although it was not possible to detect the fungus transmission to aerial organs from seeds, it was succeeded in artificially infected seed corn with Et by exposing the seed to the mycelium of the fungus. The active ingredient iprodione was the most powerful to control Et, followed by fludioxonil and thiram. The fungicides carbendazim, metalaxyl and captan were classified as non-fungitoxic the Et. The IC50 values, may be used as reference values for future studies